Forced Convective Heat Transfer and Fluid Flow Chracteristics in Curved Ducts - Chandratilleke, Tilak; Nadim, Nima (InTech, 2012)
Fluid flow through curved ducts is influenced by the centrifugal action arising from duct curvature and has behaviour uniquely different to flow within straight ducts. In such flows, centrifugal forces induce secondary flow vortices and produce spiralling fluid motion within curved ducts. Secondary flow promotes fluid mixing with intrinsic potential for thermal enhancement and, exhibits possibility of fluid instability and additional secondary vortices under certain flow conditions. Reviewing the published work on numerical and experimental studies, this chapter discusses the current knowledge-base on secondary flow in curved ducts and, identifies the deficiencies in analyses and fundamental understanding. The chapter then presents an extensive research study capturing advanced aspects of secondary flow behaviour and associated wall heat transfer processes for both rectangular and elliptical curved ducts.This study develops a new three-dimensional numerical model incorporating helicity approach and curvilinear mesh that is validated against published data to overcome current modelling limitations. Flow patterns and thermal characteristics are obtained for a range of duct aspect ratios, flow rates and wall heat fluxes. Results are analysed for parametric influences and construed for clearer physical understanding of the flow mechanics involved. The study formulates two analytical techniques whereby secondary vortex detection is integrated into the computational process with unprecedented accuracy and reliability. The vortex inception at flow instability is carefully examined with respect to the duct aspect ratio, duct geometry and flow rate. An entropy-based thermal optimisation technique is developed and tested for fluid flow through curved rectangular and elliptical ducts.